The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10709-007-9169-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and karyotype differentiation in Paratelmatobius and Scythrophrys (Anura, Leptodactylidae)

Abstract: Paratelmatobius and Scythrophrys are leptodactylid frogs endemic to the Brazilian Atlantic forest and their close phylogenetic relationship was recently inferred in an analysis that included Paratelmatobius sp. and S. sawayae. To investigate the interspecific relationships among Paratelmatobius and Scythrophrys species, we analyzed a mitochondrial region (approximately 2.4 kb) that included the ribosomal genes 12S and 16S and the tRNAval in representatives of all known localities of these genera and in 54 othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
(41 reference statements)
0
14
0
10
Order By: Relevance
“…The family was resurrected by Grant et al (2006) to include the genera Edalorhina, Engystomops, Eupemphix, Physalaemus, Pleurodema, Pseudopaludicola, and Somuncuria. However, conflicting results were obtained in other phylogenetic analyses (Frost et al, 2006;Lourenço et al, 2008) so that the relationships of these taxa with the other Leptodactyliformes (sensu Frost et al, 2006) should be reassessed. We chose this group because it shows remarkable variation in the oral apparatuses of even closely related species, in some cases also involving characters that are not present in the generalized larval oral discs (Fig.…”
Section: Introductionmentioning
confidence: 94%
“…The family was resurrected by Grant et al (2006) to include the genera Edalorhina, Engystomops, Eupemphix, Physalaemus, Pleurodema, Pseudopaludicola, and Somuncuria. However, conflicting results were obtained in other phylogenetic analyses (Frost et al, 2006;Lourenço et al, 2008) so that the relationships of these taxa with the other Leptodactyliformes (sensu Frost et al, 2006) should be reassessed. We chose this group because it shows remarkable variation in the oral apparatuses of even closely related species, in some cases also involving characters that are not present in the generalized larval oral discs (Fig.…”
Section: Introductionmentioning
confidence: 94%
“…A study using DNA sequence data from 2 mitochondrial genes (16S + 12S ribosomal RNA) suggests that A. ruthveni is most closely allied to the family Centrolenidae [Austin et al, 2002]. Further molecular phylogenetic studies analyzing the 16S + 12S rRNA genes and the intervening transfer RNA valine gene [Lourenço et al, 2008], or the mitochondrial 16S + 12S rRNA and NADH-1 genes, as well as the nuclear genes c-myc , POMC and RAG-1 [Guayasamin et al, 2008], have confirmed that A. ruthveni is a sister taxon to the family Centrolenidae. This is consistent with Noble [1931] who originally designated A. ruthveni as an edentate centrolenid.…”
Section: Discussionmentioning
confidence: 99%
“…However, our knowledge is still incipient, and the total number of species should increase in the upcoming years (e.g., Figure 9 an unnamed new species and Figure 10 a newly described species), as indicated by the species accumulation curve (Figure 8). Fundamentally, this occurs for two reasons: a larger number of researchers working on the subject and the use of new methodologies (e.g., bioacoustics, cytogenetics, and molecular biology) that allow the recognition of cryptic species (e.g., Faivovich et al 2004, Lourenço et al 2007, Toledo et al 2007, Berneck et al 2008.…”
Section: Discussionmentioning
confidence: 99%